Peningkatan Legalitas dan Keberlanjutan UMKM Melalui Pengurusan Nomor Induk Berusaha di Kelurahan Kalijudan, Kota Surabaya - Puspita Dewi, Aprilia; Iryanti, Endang (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Business legality is an important aspect for the sustainability of Micro, Small, and Medium Enterprises (MSMEs). However, there are still many MSME players in Kalijudan Village, Surabaya City, who do not have a Business Identification Number (NIB) as an official business identity. This community service activity aims to increase understanding and assist MSME operators in the process of issuing NIBs through the Online Single Submission (OSS) system. The methods used include socialization, technical assistance, and evaluation of NIB issuance results. Of the 20 MSME operators who were assisted, 12 successfully issued NIBs after participating in the assistance program, while the other 8 already had NIBs. The results of the activity showed an increase in awareness of the importance of business legality in obtaining access to financing, training, and marketing networks. Thus, this activity was effective in strengthening legality and encouraging economic independence among the community in Kalijudan Village.